THE JARGONS USED BY BALINESE DANCER OF FEMALE AT SANGGAR SENI MANIK UTTARA - Stuti, N.N.W.; Ramendra, D.P.; Utami, I.A.M.I. (Language and Education Journal Undiksha, 2018)
This study aimed to know the form of jargons used by Balinese Dancer of female at Sanggar Seni Manik Uttara, to know the meaning of each jargons used by Balinese Dancer of female at Sanggar Seni Manik Uttara, and to know the function of Jargons used by Balinese Dancer of female at Sanggar Seni Manik Uttara. The main instrument of this study was the researcher itself which supported by the recorder, camera, interview guide and observation to collect the data. From the explanation of the Instructor and student of Balinese Dancer, there are found 41 jargons which consists of 17 compounding, 2 reduplications, and10 Affixations of word formation process, then there are 10 nouns and 2 verbs of word classes. Those jargons were used to make the communication among the Balinese Dancer easier. Moreover, it can build the solidarity of each team when talk about the Balinese Dance.